A comprehensive index to bag-ong kusog - Cabellon, Wilhelmina Bono
This is comprehensive index to all teh issues of Bag-ong kusog, a Sugbuanon newspaper, from 1915-1927. This newspaper was published in Cebu from 1915-1941 and was considered the leading periodical of its time. It reached a peak circulation of 7,000. Behind the popularity of BAG-ONG KUSOG was its publisher-editor, Vicente Rama, a prolific fiction writer and journalist and an honored public servant. This newspaper regularly provided space for literary pieces and like the other Sugbuanon periodicals, was responsible for encouraging and fostering Sugbuanon literature. The index is divided into two parts. The first part is the author index. This includes an alphabetical listing of the authors of news, essays, short stories, poems, books, book reviews, speeches regular columns and other materials published in BAG-ONG KUSOG from 1915-1927. Under each author, the works are arranged in alphabetical order by the first word, initial article being disregarded. The second part is the subject index. Entries are arranged also alphabetically. each entry includes the subject heading, the title of the article or a summary of the news in English followed by the author's name, page, column, date of publication, and an indication of the type of illustration, if available.